IDENTIFIKASI PERSEPSI RESPONDEN TERHADAP WISATA ALAM PUSRI, DANAU RANAU OKU SELATAN, PROVINSI SUMATERA SELATAN - Setiyawan, Eko; Winarno, Gunardi Djoko; Fitriana, Yulia Rahma; Yuwono, Slamet Budi (Jurusan Kehutanan, 2021)
The tourist's perception is essential in developing tourism as a base on decision-making for tourism management. The purpose of this study was to identify respondents' perception of facilities and services, accommodation, infrastructure, nature, and environment in Pusri Lake Ranau Nature Tourism. Data collection was implemented by direct observation method and closed interview questionnaire. The data obtained is then descriptively qualitatively analyzed. The results showed that respondents' perceptions gave a varied assessment of Pusri Danau Ranau Nature Tourism for each aspect of the assessment, including natural and environmental aspects of 3.91 (quite good), accommodation aspect of 3.45 (quite good), infrastructure aspect of 3.22 (quite good) and aspects of facilities and services of 3.38 (quite good). The element that must be looked at is in the environmental hygiene sector because respondents are still not satisfied with the element, which can be seen from the average value of cleanliness of 2.91 (not good), waste management of 2.71 (not good), and toilets of 2.54 (not good). Environmental cleanliness needs to be considered so that tourism remains beautiful and the improvement of facilities such as the procurement of garbage boxes.